Original paperSELF-RATED PHYSICAL ACTIVITY LEVEL ACROSS EUROPE – POLAND AND OTHER EUROPEAN COUNTRIES - Piątkowska, M. (Biology of Sport, 2012)
Physical inactivity has become a serious public health problem as it contributes to major non- communicable diseases. Increasing activity levels has beneficial effects on musculoskeletal health and mental health as well. In Poland there are a few studies which refer to the physical activity (PA) of the overall society and which are based on an international questionnaire, thus enabling comparative analysis. The aim of the study was to assess the PA level of the Polish society and to examine fields of their activity and intensity of them in order to compare the data with fifteen European countries. A survey based on computer-assisted personal interview (CAPI) was carried out in Poland in November 2006. A random sample of Polish adults (n=1028) was selected and divided according to demographic criteria. PA was estimated by a short version of the International Physical Activity Questionnaire (IPAQ). In the last seven days 53.4% of the Polish society reported no vigorous PA whereas in the European sample the percentage was significantly higher (57.4%). For the PA of moderate level of intensity 39.8% of the Polish respondents reported no such PA; in the European sample the percentage was 40.8%. Only 12.8% of the Polish respondents reported not having walked in the past week, whereas in the EU the percentage was 17.1%. It must be noted that in all aspects the results were varied in the studied countries. These observations indicate a need for urgent actions to promote HEPA across EU member countries and in particular the least active member states. The present study is the first referring to PA of the whole Polish population, based on a representative sample and an international standardised questionnaire. The data confirm that the PA level of the Polish society is not as low as it has been shown in many studies.